Mechanism of the cardioprotective effect of transforming growth factor beta 1 in feline myocardial ischemia and reperfusion. - Lefer, A M (1993)
We studied the effects of transforming growth factor beta 1 (TGF-beta 1) in a feline model of myocardial ischemia (1.5 hr) and reperfusion (4.5 hr). Myocardial ischemia followed by reperfusion resulted in severe myocardial injury, endothelial dysfunction, high cardiac myeloperoxidase activity indicative of neutrophil accumulation in the ischemic myocardium, and significant neutrophil adherence to the ischemic coronary endothelium. In contrast, intravenous administration of TGF-beta 1 (20 micrograms/kg) 30 min prior to reperfusion significantly attenuated myocardial necrosis (13.8% +/- 3.5% vs. 32.2% +/- 2.9% of area-at-risk, P < 0.01) and attenuated endothelial dysfunction (P < 0.01) associated with ischemia-reperfusion. Moreover, myeloperoxidase activity in the ischemic myocardium was significantly lower than vehicle controls (0.2 +/- 0.1 vs. 1.7 +/- 0.3 units/100 mg of tissue, P < 0.01) and neutrophil adherence to ischemic coronary endothelium was significantly (P < 0.01) attenuated in TGF-beta 1-treated cats. These results demonstrate that TGF-beta 1 exerts a significant cardioprotective effect in a feline model of myocardial ischemia and reperfusion. The mechanism of this protective effect appears to relate to endothelial preservation by TGF-beta 1 inhibiting circulating neutrophils from adhering to the endothelium, a critical step in neutrophil-induced reperfusion injury.